1992
DOI: 10.1161/01.cir.86.6.1710
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, placebo-controlled, randomized trial of intravenous streptokinase and angioplasty versus lone angioplasty therapy of acute myocardial infarction.

Abstract: Adjunctive intravenous streptokinase therapy does not enhance early preservation of ventricular function, improve arterial patency rates, or lower restenosis rates after PTCA therapy of acute MI. Hospital course is longer, more expensive, and more complicated. For these reasons, PTCA therapy of acute MI should not be routinely performed with adjunctive intravenous streptokinase therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(47 citation statements)
references
References 42 publications
2
41
2
2
Order By: Relevance
“…[1][2][3][4][5][19][20][21][22] It has been reported that rescue PTCA has a poor acute result, [23][24][25] so the combination of thrombolysis and mechanical angioplasty is not accepted as an established modality, despite several studies demonstrating that the effectiveness and safety of ICT prior to PTCA are enhanced in selected patients with a large thrombus. 26,27 Once angiographic no-flow occurs during the procedure, achieving flow restoration is not easy and if no-flow persists there is a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][19][20][21][22] It has been reported that rescue PTCA has a poor acute result, [23][24][25] so the combination of thrombolysis and mechanical angioplasty is not accepted as an established modality, despite several studies demonstrating that the effectiveness and safety of ICT prior to PTCA are enhanced in selected patients with a large thrombus. 26,27 Once angiographic no-flow occurs during the procedure, achieving flow restoration is not easy and if no-flow persists there is a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in cardiogenic shock were excluded or poorly represented in most trials. The fibrinolytic agent used was streptokinase in two trials (8,9), alteplase (rt-PA) in two trials (10,11) and tenecteplase (TNK) in three trials (12)(13)(14). In the ASSENT-4 and WEST studies (study acronyms are spelled out in Appendix 1), 20% and 40% of patients were enrolled in the prehospital setting, respectively.…”
Section: Pci Facilitated By Fibrinolytic Therapy Alonementioning
confidence: 99%
“…The risk of reinfarction was 2.0% to 7.0% with facilitated PCI and 1.0% to 3.7% with nonfacilitated PCI. In addition, facilitated PCI had no effect on the following surrogate end points: ST segment resolution at 60 min (GRACIA-2 [12], ADVANCE MI [15]), infarct size (GRACIA-2, BRAVE [16]), convalescent LVEF (SANI [8], PACT [10], PRAGUE-1 [17], GRACIA-2, BRAVE [16]), exercise stress test performance (PACT [10]) or MACE up to one year of follow-up (LIMI [11], PACT [10], PRAGUE-1 [18]). …”
Section: Pci Facilitated By Fibrinolytic Therapy Alonementioning
confidence: 99%
“…A strategy of thrombolysis combined with transfer for immediate or early PCI was not supported by 3 level-1 randomized trials, 27-29 one level-2 30 and one level-7 trial, 31 and several nonrandomized studies or secondary analyses of trials. Several level-1 meta-analyses 32-34 also showed no benefit of immediate or early PCI.…”
Section: Studies Showing Neutral Effect or No Benefit By Qualitative mentioning
confidence: 99%
“…20,27 In some studies, patients in the control group routinely underwent delayed PCI, 21,28 whereas in others, patients in the control groups were treated medically unless they had spontaneous or inducible ischemia. 20,27 For studies in which all control-group patients underwent primary PCI, 14,26,31,40 no inference could be made on the efficacy of immediate or early angioplasty after thrombolysis compared with delayed angioplasty, and only the safety and feasibility of this approach was evaluated. The symmetry seen in the funnel plots and the large number of published studies with neutral or opposing results suggest that publication bias was unlikely to have had a major impact on the findings of this systematic overview.…”
Section: 45mentioning
confidence: 99%